THE LINKAGE MODEL BETWEEN UNIVERSITIES, RESEARCH INSTITUTES AND ENTERPRISES: ASPECTS OF EDUCATION - Tuyet, Đào Văn; Thành, Nguyễn Trung; Man, Nguyễn Xuân; Giang, Lê Trường; Quang, Trịnh Lương; Phúc, Nguyễn Xuân (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The center of Informatics - Medicine - Biology of Binh Duong University (BDU) is an interdisciplinary scientific research, technology transfer and training center that has been operating since 2015 and has initially successfully implemented the cooperation model and cooperation in scientific research, technology transfer as well as training between universities, institutions and enterprises. In this paper, we will conduct a survey using the method of combining the three fields mentioned above. The model needs to be replicated, however, its implementation and operation still face many difficulties.The problems need to be solved with the impact of the startup ecosystem and the activities of potential research groups of Binh Duong University.